(untitled) (Journal of Comparative Social Work, 2022)
This paper explores how kindergarten teachers relate to the concept of safety in the integration of refugee children. My research findings reveal that the concept of safety, or trygghet in Norwegian, is understood as emotional support and comfort accorded to children. The notion of trygghet emerges as an important value-laden concept that shapes and largely influences teachers’ everyday work, and how they relate to children and their parents. The idea of safety is traceable within an institutional discourse mediated by social technology, such as the International Child Development Programme and the Resource Centre for Violence and Trauma programmes, which have their roots in psy-discourses. My findings indicate that the construction of a potentially ‘traumatized’ refugee child is interconnected with the assumed need for safety. When using this discourse in their daily work, the kindergarten staff contribute to constructing and reproducing a specific category that I refer to as the ‘traumatized’ refugee child in need of safety. This standardized understanding risks categorizing refugee children, and highlights how professionals can get caught up in dominant discourses that universalize their routine practices.